0739 Employee Age Associates with Work-Related Sleep Outcomes. (27th April 2018) - Groenewold, N; Kavanaugh, C; Wang, H; Rhode, S; Mason, T; Williams, M; Zallek, S N
Abstract: Introduction: Tiredness in workers can lead to absenteeism, errors, and accidents in addition to negative mood, mistrust, hostility, resentment, and increased sensitivity in the workplace. Decreased work performance can have a significant impact for companies, as a recent study estimated the cost of fatigue-related productivity losses at four U.S. based companies to be $54 million dollars annually. The purpose of this study was to assess the association between employee age, sleep quality and quantity, and performance and behavior in the workplace. Methods: A sample of employees at OSF HealthCare Saint Francis Medical Center (n=573, age 18–69) completed a 20-question survey about various aspects of sleep, including quantity and quality, and aspects of the workplace, including mood, efficiency, and interactions. Univariate and multivariate analyses were completed, and age was treated as a continuous variable. Results: Subjects who reported unrefreshing sleep (n=325, 56.7%), when compared with subjects who reported refreshing sleep (n=248, 42.3%), were more likely to report sleepiness, tiredness, or fatigue affecting workplace mood and interactions (n=48, n=11 respectively, (14.77%, 4.44%) p<.0001). Younger subjects were more likely than older subjects to report unrefreshing sleep (p=.0002), but there was no difference in reported duration of sleep between younger and older subjects (p=.219). Additionally, younger subjects were more likely than older subjects to report that sleepiness affected workplace mood and interactions (p>.0001) and efficiency (p=.0023). Conclusion: The findings that younger age and unrefreshing sleep are independently associated with adverse workplace outcomes, and that younger workers are more likely to have unrefreshing sleep, suggest that it may be worthwhile to address sleep health in employees, particularly younger ones. Support (If Any):